Interpreting the Role of Parenting in Maintaining Early Childhood Mental Health: A Qualitative Study of Parents’ Perceptions in Preschool Contexts - Ni'matussilva, Fatikha (Qualitative Research in Early Childhood Education, 2026)
Early childhood mental health plays a crucial role in shaping children’s emotional, social, and cognitive development. Parenting is considered a key factor in creating a supportive environment that fosters children’s psychological well-being. This study aims to interpret the role of parenting in maintaining early childhood mental health based on parents’ perceptions in preschool contexts. A qualitative approach with a phenomenological design was employed to explore parents’ lived experiences and meanings related to caregiving practices. The participants consisted of 10 kindergarten teachers in Brebes Regency, Indonesia, selected through purposive sampling. Data were collected through in-depth interviews and documentation and analyzed using thematic analysis. The findings reveal that parents perceive parenting as the primary foundation for children’s mental health, emphasizing the importance of emotional support, warm communication, and consistent caregiving. Parents also experience challenges in balancing emotional protection and children’s social interaction needs, which require adaptive parenting strategies. Furthermore, collaboration between parents and teachers is identified as a critical factor in supporting children’s emotional development, as it strengthens continuity between home and school environments. Early childhood education is perceived not only as a learning space but also as a supportive and healing environment that contributes to children’s emotional stability. This study highlights the importance of integrating parenting practices and educational support systems to promote children’s mental health. The findings provide theoretical contributions by emphasizing parents’ subjective experiences and offer practical implications for developing context-sensitive parenting programs and policies in early childhood education.